Edukasi Stunting Berbahasa Khas Suroboyoan Sebagai Upaya Pencegahan dan Penurunan Kejadian Stunting di Surabaya - Efendi, Ferry; Nihayati, Hanik Endang; Indarwati, Retno; Pradipta, Rifky Octavia; Rahayu, Fitri Kurnia; Hidayati, Nurul (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Stunting is a global health issue that significantly impacts a country's well-being. Community empowerment, particularly through the role of posyandu (integrated health post) cadres and mothers of young children, is crucial in stunting prevention efforts. This community service program aimed to prevent stunting by educating the community using a health information pocketbook written in the local Suroboyoan language. Conducted in RW 5, Pacar Kembang Subdistrict, Surabaya, the program was attended by 30 participants, including posyandu cadres, pregnant women, and mothers of young children. The Asset-Based Community Development (ABCD) method was implemented through socialization and interactive discussions. The program successfully increased the participants' average knowledge score from a pre-test score of 69.7 ± 15.19 to a post-test score of 86.7 ± 9.58, with a p-value of 0.000 (Wilcoxon test), indicating a statistically significant improvement. The use of a pocketbook based on the local language proved effective in enhancing participants' understanding of stunting prevention. This approach is not only locally relevant but also has the potential to be replicated in other areas with cultural adaptations. Additionally, this model can be integrated into community health programs to support sustainable efforts in stunting prevention and improving public health literacy.